A rare variation of celiac trunk and hepatic artery complicating pancreaticoduodenectomy: A case report and literature review. Issue 48 (December 2017) - Ye, Zhou; Ye, Song; Zhou, Dongkai; Zheng, Shusen; Wang, Weilin
Abstract: Rationale: Anatomical variations of the celiac trunk and the hepatic artery are of considerable importance in hepatopancreatobiliary surgery, liver transplants, and radiological abdominal interventions. Patient concerns: Here, we report a 57-year-old man with 2 weeks of painless progressive jaundice. Preoperative imaging and cytology brush results suggested an ampullary tumor and common hepatic artery anomaly (CTA) was reported. The patient underwent pancreaticoduodenectomy (PD). Intraoperatively, the CHA and gastroduodenal artery (GDA) were abnormal. The CHA emerged from the superior mesenteric artery (SMA). Computer tomography angiography (CTA) was performed postoperatively; surprisingly, the left gastric artery (LGA) and splenic artery (SA) arising from the anterior wall of the abdominal aorta replaced the normal structure of the celiac trunk, and an accessory left hepatic artery (LHA) emerged from the LGA. Diagnoses: The patient was diagnosed with cholangiocarcinoma and accompanying extremely rare variation of celiac trunk and hepatic artery. Interventions and outcomes: The patient underwent PD and had an uneventful postoperative evolution. There was no recurrence of the tumor and with normal liver function during the 10-month follow-up. Interventions: The patient underwent PD and had an uneventful postoperative evolution. Outcomes: There was no recurrence of the tumor and with normal liver function during the 10-month follow-up. Lessons: Surgeons must keep in mind that arterial variation may be present in the vascular structures intraoperatively, even if it was not revealed in preoperative imaging. The preoperative identification of arterial variation and its relationship with the tumor is necessary to avoid intraoperative vascular injury and complications after surgery.